Humanization of care in the Intensive Care Unit: integrative literature review (Research, Society and Development, 2022)
Intensive Care (ICU) is an Intensive Care Unit (ICU) where high-complexity equipment and a specialized multidisciplinary unit are located, where they are specialized in patients who require a serious health condition, but who have a chance of survival. Thus, the humanization policy (PNH), how to achieve goals in health services, the identification of health needs, appreciation of the user, workers and managers, within the ICU it is important that the practice of humanization of all patients, also needs that within the multidisciplinary team. The current study aims to show the practice of humanization of care in the ICU based on the scientific literature. This is an integrative literature review, carried out in February and March 2022 through electronics in the SciELO and Lilacs databases. The strategies allowed to identify 256 articles, applying the inclusion criteria, 244 were excluded, 12 articles were not selected because they met all the requirements. The results show that there are difficulties in the implementation of care, but despite this, professionals have a good perspective of approaching this perspective, effectively helping in the practice of effective strategies. Therefore, it is concluded that, despite the difficulties for the practice of such a policy, research shows the enormous benefits that the humanization of care for the patient within the intensive care unit, among them, the increase in suffering.